Al-Ṭarīqah al-Naqshabandīyah fī Minangkabau: Tarjamat Kitāb al-Sa‘ādah al-Abadīyah li Shaykh ‘Abd al-Qadīm - Hasyim, Arrazy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
This article is a study about a Malay version of the 'Abd al-Majid al-Khani al-Khalidi's al-Sa'adah al-Abadiyah, written by Syekh Mudo Tuanku 'Abd al-Qadim of Belubus, Payakumbuh, West Sumatera. The manuscript which is used as the source of this study is a copy written by 'Abd al-Jumin of Suayan from Lima Puluh Kota, West Sumatra. This article uses philological approach in addition to Sufism approach on the substance of the kitab. These approaches are used to explore the ideas of Sufism of 'Abd al-Qadim who was known as a Naqshabandiyah sufi of Minangkabau. Thus, this study focuses on the biographical portrait, activities, and works of 'Abd al-Qadim.DOI: 10.15408/sdi.v18i1.442